Community structure analysis of family strombidae (Mollusca Gastropoda) in four seagrass sites in Taklong Island National Marine Reserve , Guimaras - Coopera, Elaine Mae N
This study determined the species composition, abundance, density, diversity, richness, evenness, dominance, similarity, biomass and size structure of Family Strombidae in four seagrass sites in Taklong Island, National Marine Reserve (TINMR), Nueava Valencia, Guimaras from November to December 2017. The method used was belt transect. All strombid individuals encountered were handpicked, measured by length and weight, described and identified. A total of 7 species were recorded namely, Lambis lambis Linnaeus 1758, Strombus aurisdianae Linnaeus 1767, S. gibberulus Linnaeus 1758, S. labiatus Röding 1798, S. luhuanus Linnaeus 1798, S. mutabilis Swainson 1821 and S. urceus Linnaeus 1758. The most abundant species were S. urceus and S. mutabilis. Lambis lambis had the highest biomass and size structure. The densest and most diverse site was Calaparan where all seven species were recorded. Highest mortality of strombids was recorded in Piagau.